The effect of static and dynamic muscle stretching as part of warm-up procedures on stretching on isokinetic strength, functional movement screen, flexibility and agility in Korean national foil fencers - Kim, B.-S.; Lee, J.-S. (International Journal of Applied Sports Sciences, 2021)
The purpose of this study was to investigate the effect of combined static and dynamic stretch as part of warm-up procedures on isokinetic strength, functional movement screen (FMS), flexibility, and agility in Korean national foil fencers. Twelve Korean fencers (mean age 29.3±3.6yrs, Career: 16.6±3.1yrs, Height: 171.4±9.5cm, Weight: 67.3±12.4kg) participated in this study (Male: 7, age 30.0±3.2yrs, Career: 16.7±2.2yrs, Height: 177.1±8.1cm, Weight: 75.1±9.9kg; Female: 5, age 28.4±4.4yrs, Career: 16.4±4.3yrs, Height: 163.4±3.9cm, Weight: 56.3±4.1kg). Fencers measured FMS, isokinetic strength of knee joint, flexibility, agility at pre (1-week) and post (4-week). Fencers performed a warm-up program three times a week for four weeks. As a results, FMS scores (11.8±2.3 to 14.4±1.6, p<0.05), strength of dominant knee flexors (115.5±26.0 to 126.0±26.6, p<0.05), change-step jump (66.0±6.8 to 69.4±5.6, p<0.05), trunk forward flexion (12.0±7.7 to 13.9±6.5, p<0.05) were significantly higher in post-test than pre-test, respectively. However, the results for front-rear step, trunk backward extension were not significant differences between pre-test and post-test. These results suggest that the fencing-specific warm-up program based on stretching is effective on strength of knee flexors, agility by increasing flexibility, improving stability, mobility.